A Study of Translanguaging Practices in an EFL Classroom in Indonesian Context: A Multilingual Concept - Nihta V. F. Liando; Devilito Prasetyo Tatipang; Fergina Lengkoan (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
In a multilingual society there is of course the teaching of a second (and perhaps third) language. At the educational level of Indonesia, English as a foreign language or EFL explicitly requires a lot of interaction in speaking, as well as in language skills in general. Translanguaging is a form of multilingual practice in the context of multilingual education where students must be given equal rights to develop their language potential. Seeing the complexity of the learning process that must be covered in teaching English in a multilingual situation, therefore the purpose of this research is to reveal the benefits, functions, and purposes of Translanguaging in the learning process. This research is descriptive research with a qualitative approach, where the researcher is the key instrument of data. Data collection techniques are carried out by triangulation (combined) of observations, interviews, and study documents. The qualitative research results emphasize meaning rather than generalization. Translanguaging merupakan salah satu bentuk praktik multibahasa dalam konteks pendidikan multibahasa dimana siswa harus diberikan hak yang sama untuk mengembangkan potensi bahasanya. Melihat kompleksitas proses pembelajaran yang harus dicakup dalam pengajaran bahasa Inggris dalam situasi multibahasa, maka tujuan dari penelitian ini adalah untuk mengungkap manfaat, fungsi, dan tujuan Translanguaging dalam proses pembelajaran. Dengan menggunakan desain studi kasus, pengumpulan data menggunakan teknik wawancara dan observasi langsung. Temuan riset ini menunjukkan tiga jenis penerjemahan yang digunakan oleh guru selama mengajar. Jenis-jenis translanguaging tersebut adalah intra-sentential translanguaging, intersentential translanguaging, dan tag translanguaging, dengan empat tujuan yang saling berkaitan yang dapat dimanfaatkan untuk mendeteksi hasil pembelajaran siswa.